Literature review on technology transfer and documentation / Josiun Kolongan - Kolongan, Josiun (Faculty of Information Management, 2002)
Successful Technology Transfer and documentation: A Literature Review, The technology transfer concern about patent, trademarks, copyright. Many government, non-government, and commercial organizations are currently involved with development in less developed areas of the world, often inhabited by indigenous peoples. Energy is a primary concern in these areas, as the addition of electricity can increase the standard of living, and improve health, education, and the potential for economic growth. Sometimes the transfer of energy technologies is not successful. To discover why this is so, a literature search was conducted to explore new technologies that were integrated into indigenous populations. From these, some of the issues associated with technology transfer were uncovered. It was found that communication between the developer and the community is invaluable. The developer must determine whether or not a community wants new technology, the intended uses of the technology to avoid future disappointment, and understand the local culture as much as possible. Independent of the particular technology, clear communication and a strong understanding of the community on the part of the developer are the two most urgent issues for successful technology transfer.